Shamba Shape Up: Series 1: Munda Make over TV show in Zambia - Mediae Company (2022)
Through Mediae, CGIAR is supporting the scale up of the Shamba Shape up tv show to the Zambian Market. The show will present agro-advisories, and bundles of digital and agriculture services, whilst providing advisories on conservation agriculture, climate information services and literacy on finances and Weather Index Insurance for agriculture to farmers.